IMPLEMENTASI PERJANJIAN INTERNASIONAL TENTANG PERUBAHAN IKLIM DI INDONESIA DALAM OTONOMI DAERAH DAN PEMBANGUNAN BERKELANJUTAN - Maret Priyatna (Indonesian Journal of Dialectics, 2011)
Global warming and climate change in the world cause the degradation of environmental quality.  This problem is a modern and complicated and source by development activity and policy of the state related environmental protection and management. International corporation through the international convention is one of effort can be done to solve that problem and implemented by the United Nations Framework Convention on Climate Change. Indonesia legal system regulate the ratification of the international convention, this process face a lot of difficulties for imply especially ini environmental matter. Regional autonomy give opportunity and also challenge for implementation of international convention in unity state for guarantee the sustainable development for present and next generation.Descriptive Analytical methodology is used for this research in order to gain a comprehensive idea about climate change and environmental law. The law and regulation approach used is legal normative, systematic conducted toward the related constitution. Technique of data collection was done through literature study and field research to collect primary and secondary data.International convention related to climate change ini Indonesia can not be apply effectively in local/ regional, because of there is no regulation related to ratification thought international convention related to environmental matter in law and regulation shape for local government refer to comply the local policy related to it. In order to sustainable development implementation, law related to environmental protection and management must be the umbrella provision for every activities in Indonesia including compliance and enforcement environmental law related to climate change for protection environmental function  for   present and next generations.